Punching shear repairing of two-way solid slab subjected to high temperature using CFRP rope considering different configurations - Ahmed M. Ashteyat; Ala’ Taleb Obaidat; Ibrahim Al Hazmi; Ahmad Al-Khreisat (Journal of Asian Architecture and Building Engineering)
Flat slabs are increasingly utilized in multi-story structures, including office buildings and parking facilities. However, the necessity for punching shear reinforcement arises due to factors such as design deficiencies, fire exposure, non-compliance with updated codes, or increased vertical loading. This study examines the behavior of nine two-way slabs (1050 × 1050 × 70 mm) supported by steel plate columns (150 × 150 × 50 mm). Seven slabs were heated to 600 °C for 3 hours. Six of these slabs were then rehabilitated using near-surface mounted carbon fiber reinforced polymer (NSM-CFRP) ropes and strips, applied in different configurations (orthogonal and radial). Results indicated that thermal exposure led to a significant reduction in ultimate load capacity, up to 48%, increased deflection, and enhanced ductility relative to the control. The incorporation of NSM-CFRP ropes enhanced the ultimate capacity by 11% to 54% compared to the thermally damaged specimens. The most effective configuration involved a single rope in an orthogonal layout, which showed an increase in the ultimate capacity by 30%, while additional ropes provided no significant capacity gain, likely due to reduced effectiveness from close spacing. A finite element model developed in ABAQUS showed strong agreement with experimental data, offering valuable insights for optimizing reinforcement strategies in flat slab construction.